Interfacial and Structure-Property Relationships in Poly(lactic acid)/Polyaniline Bio-nanocomposites Incorporating Green-synthesized ZnCoS Nanoparticles - Pekdemir, Mustafa Ersin; Babakr, Karukh Ali; Pekdemir, Sibel Selcuk; Tas, Nilay Akkus; Cetik, Seymanur; Qader, Ibrahim Nazem; Tuncer, Hulya (Springer, 2026)
Biodegradable polymer nanocomposites containing functional nanoparticles have attracted growing interest because interfacial phenomena can strongly influence macroscopic properties. In this study, ZnCoS nanoparticles were synthesized by a green microwave-assisted route and incorporated into a poly(lactic acid)/polyaniline (PLA/PANI) matrix at 1 wt%, 5 wt%, 10 wt%, and 20 wt% loadings. Dynamic light scattering indicated an average hydrodynamic diameter of 195.35 nm, suggesting partial aggregation in the dispersion. The ATR-FTIR spectra indicated nanoparticle-polymer interfacial interactions without evidence of chemical alteration of the polymer backbone. X-ray diffraction showed a non-monotonic crystallinity trend, with an initial decrease at low nanoparticle loading followed by an increase at higher loadings, consistent with heterogeneous nucleation. Thermal analysis showed improved thermal stability, with the char yield increasing from 4.30% for the neat PLA/PANI to 10.70% at 20 wt% ZnCoS, while the glass-transition and melting temperatures remained essentially unchanged. Dielectric and AC electrical measurements showed a frequency-independent conductivity plateau at low frequencies, followed by dispersive behavior at higher frequencies, consistent with hopping-type charge transport. At low ZnCoS loadings, interfacial charge trapping reduced the AC conductivity and dielectric loss, whereas higher loadings enhanced interfacial polarization and partially recovered the conductivity. The dielectric spectra showed clear Maxwell-Wagner-Sillars polarization and broad relaxation, indicative of a distribution of relaxation times, underscoring the key role of interfacial effects in the electrical response. Overall, the results clarify the nanoparticle-polymer interfacial contributions in biodegradable nanocomposites and support their relevance in functional and transient material systems.
Keywords: Zncos Nanoparticles; Poly(Lactic Acid)/Polyaniline (Pla/Pani) Nanocomposite; Green Synthesis; Shape-Memory Behavior; Dielectric Properties